The Effect of Wage Subsidies on Piece Rate Workers: Evidence from the Penny Per Pound Program in Florida - Hyejin Ku (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2018)
This paper studies a fair trade program in which consumers provide a wage subsidy (bonus) to piece-rate tomato pickers. The total subsidy - determined by sales to participating buyers - is divided among workers based on their relative output: a worker who produces more gets a larger share of the bonus. Although seemingly mimicking the existing piece-rate pay scheme, the mechanism associated with the bonus payment is really a relative performance evaluation, as the size of total bonus is exogenous and invariant to workers' effort. Therefore, for a given sized subsidy, the combined total (or per worker average) utility gains would become the largest if the workers keep their efforts at the pre-program level. Empirical analysis shows that worker effort (and hence productivity) increases substantially in response to the program, suggesting that currently, workers' combined gains per dollar of subsidy are not being maximized. Alternative distribution schemes are discussed.
Keywords: J24; J31; J38; M52; O12; 330; piece rate; subsidy; fairness; tragedy of the commons; natural experiment